Training Model Designed to Strengthen and Improve the Pass for Juniors 10 – 12 Years - S. Teris; I.I. Lakotos; V. Koronas (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
The purpose of this study is represented by the theoretical and methodical elaboration of a material intended for continuous use by coaches and teachers working with groups of juniors aged between 10 and 12 years. We propose an intervention in the training plan, starting with the study of specialized literature in the field of football and aiming to improve the methodology for teaching specific means but also the evaluation process of a model to be used. Also, the intervention in the training plan has as a general objective the consolidation of the procedures and technical elements specific to the football game, but also the development of all motor qualities. The study is based on collaboration with coaches in this area who work with children aged 10 to 12 years, the goal being to conduct a theoretical analysis of the content of the passing game, to model the content of the training, and to verify the effectiveness of a model intended to strengthen and perfect the passing game at the aforementioned age.